(untitled) (Bangladesh Critical Care Journal, 2016)
Difficult intubation and difficult mask ventilation are not uncommon in ICU. When intubation in ICU turns out to be difficult, chances of complications may be more due to various reasons like poor physiological reserve and physical status of patient, inadequate experience of operator, unavailability of help from airway experts and certain airway adjuvants. The cannot intubate cannot oxygenate (CICO) situation is the most feared complication in airway management, as it can lead to hypoxic brain damage and immediate cardiac arrest leading to death unless situation is rapidly resolved. Emergency cricothyroidotomy can come handy in such potentially life-threatening situations. Cricothyroidotomy and not tracheostomy is the recommended technique of choice for front of neck access in CICO situations with increasing hypoxemia. This article deals with the complexities of airway management in ICU, the various tools and techniques for performing emergency front of neck access by both surgical and percutaneous cricothyroidotomy including ventilation techniques and the current recommendations for performing this procedure. Considering the life saving potential of this technique, every anaesthesiologist, intensivist, or other physician dealing with airway management should be well versed with this procedure. Bangladesh Crit Care J September 2016; 4 (2): 114-122